Studies on mechanical property and wear behaviour of AA7075 hybrid composites prepared by a conventional casting method. (December 2021) - Vignesh Kumar, V; Raja, K; Ramkumar, T; Selvakumar, M; Senthil Kumar, TS
The research article addresses the reciprocating wear behaviour of hybrid AA7075 reinforced with boron carbide and boron nitride through a stir-casting technique. The experiment involved varying wt.% of the secondary particle boron carbide (3, 6 and 9) while boron nitride (3) was kept as constant. The hybrid composites were characterised using scanning electron microscopy coupled with energy dispersive spectroscopy. The hardness and tensile behaviour of the hybrid composites were evaluated. Reciprocating wear behaviour of the hybrid composites were examined using a tribometer by varying the wear parameters such as load and sliding distance. The results revealed that AA7075/6boron carbide/3boron nitride had better hardness, tensile and wear properties. The surface morphology of the wear samples was analysed using SEM.